Rekonstruksi Pengaturan Restorative Justice Dalam KUHAP 2025 Berbasis Kepastian Hukum - Nurushobbach N; Mega Dewi Ambarwati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The concept of Restorative Justice presents as an alternative paradigm that views criminal acts as a social conflict that causes harm to victims, perpetrators, and society. The mechanism for restorative justice is regulated in Law Number 20 of 2025 concerning the Criminal Procedure Code, namely in Articles 79 to 88. Restorative Justice regulations are regulated in the regulations of law enforcement agencies, namely Perja No. 15 of 2020, Perpol No. 8 of 2021 and Perma No. 1 of 2024. This study aims to examine whether the restorative justice regulations in the 2025 Criminal Procedure Code have guaranteed legal certainty and how the design of the reconstruction of restorative justice regulations in the 2025 Criminal Procedure Code guarantees legal certainty. The research method used is normative juridical, with a regulatory and contextual approach. The results of the study indicate that the restorative justice regulations in the 2025 Criminal Procedure Code still contain vague norms, inconsistencies in the regulation of authority between law enforcement officers, and the absence of a control mechanism that guarantees uniformity in the application of the law. This situation has resulted in the emergence of legal laws, potential discrimination, and reduced protection of victims' rights. The reconstruction of restorative justice regulations occurred due to the lack of clear regulations in the 2025 Criminal Procedure Code (KUHAP) that regulate the mechanism for implementing restorative justice. The 2025 Criminal Procedure Code should be the main guideline for law enforcement officers in resolving cases resolved through restorative justice mechanisms. The reconstruction of Restorative Justice regulations in the 2025 Criminal Procedure Code must guarantee legal certainty. The regulations in the 2025 Criminal Procedure Code should be clarified from the outset of a case to be resolved through restorative justice and determine who can carry out and apply restorative justice and become the main guideline for the implementation of Restorative Justice.